Second Language Interference towards First Language Use of Japanese Learners - Aziz, Zulfadli Abdul; Daud, Bukhari; Yunidar, Syafira (Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2019)
There have been many studies on first language interference towards learners’ second or foreign language learning, but not many on the otherwise. This study investigates the effects of learning Japanese as a foreign language towards learners’ first language use, Indonesian. The data for this qualitative study were obtained from five Japanese learners who had different backgrounds of Japanese learning. Observation and interview were used as the research instruments to collect the data in this study. The results were found that the learners showed foreign language effects; grammatical aspects and borrowing. In short, learning a foreign language (FL) influences learners’ first language (L1), which means that learning Japanese language had affected the learners’ first language, Indonesian. It can be concluded that learning a second or foreign language may interfere a learner’s first language.